Mediation Role of Employee Innovation and Job Satisfaction on Performance Based on Employee Creativity - Kosasih Kosasih; Yuki Kustian; Novi Elprina; I Made Wira; Eatmiati Ariska (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to examine the partial and simultaneous effects of team member creativity on innovation, job satisfaction, and performance, as well as the mediating roles of innovation and job satisfaction in the relationship between creativity and performance. Methodology: The study used a census of 137 employees as both the total population and sample. Data analysis techniques included descriptive statistics, validity and reliability tests, classical assumption tests (normality and multicollinearity), t-tests, F-tests, and path analysis. Results: The findings indicate that team member creativity has a positive and significant effect on innovation and job satisfaction. Creativity, Innovation, and job satisfaction also have significant positive effects on performance, both in parallel and in combination. Furthermore, Innovation and job satisfaction mediate the effect of creativity on performance. Conclusions: This study concludes that employee creativity significantly influences performance both directly and indirectly through innovation and job satisfaction, with both mediating variables strengthening the effect of creativity on the employee performance. Limitations: This study is limited by challenges in accurately measuring complex constructs such as creativity, innovation, and job satisfaction, as well as difficulties in establishing clear causal relationships among variables. Contributions: This study highlights the mediating roles of innovation and job satisfaction in translating team member creativity into improved performance, providing organizations with insights to enhance team member outcomes. Novelty: This study integrates creativity as an antecedent of innovation and job satisfaction, which jointly influences performance, emphasizing the mediating mechanism between these variables.